Evaluating the segmented post-rift stratigraphic architecture of the Guyanas continental margin. Issue 3 (2021) - Casson, Max; Jeremiah, Jason; Calvès, Gérôme; Goyet, Frédéric de Ville de; Reuber, Kyle; Bidgood, Mike; Reháková, Daniela; Bulot, Luc; Redfern, Jonathan
No abstract available